Application of Electronic Module Teaching Materials to Improve Student Learning Outcomes in Rhythmic Gymnastics Subject - Oktariyana Oktariyana; Oktariyani Oktariyani (UNIB Press, 2020)
The learning process that is currently taking place in the rhythmic gymnastics course in the Health and Recreation Physical Education study program at the University of Nahdlatul Ulama Lampung is still using the printed module. This is still considered ineffective and inefficient, which causes student learning outcomes in low rhythm gymnastics courses. This study aims to determine the increase in student learning outcomes between before and after being given an electronic module in rhythmic gymnastics courses. The method used in this study was one group pre-test post-test design. In this study, a pre-test and post-test were conducted to determine the increase in student learning outcomes. The increase in student learning outcomes is expressed by the N-Gain score. The results showed that the applied electronic module teaching materials could improve student learning outcomes in rhythmic gymnastics courses. Where the average N-Gain score was 56.75% with the category quite effective. Thus the application of electronic module teaching materials can improve student learning outcomes in rhythmic gymnastics courses.